The neurodegeneration mutant löchrig interferes with cholesterol homeostasis and Appl processing - Tschäpe, Jakob-Andreas (Oxford University Press, 2002)
The novel Drosophila mutant löchrig (loe) shows progressive neurodegeneration and neuronal cell death, in addition to a low level of cholesterol ester. loe affects a specific isoform of the γ-subunit of AMP-activated protein kinase (AMPK), a negative regulator of hydroxymethylglutaryl (HMG)-CoA reductase and chol esterol synthesis in vertebrates. Although Drosophila cannot synthesize cholesterol de novo, the regulatory role of fly AMPK on HMG-CoA reductase is conserved. The loe phenotype is modified by the level of HMG-CoA reductase and suppressed by the inhibition of this enzyme by statin, which has been used for the treatment of Alzheimer patients. In addition, the degenerative phenotype of loe is enhanced by a mutation in amyloid precursor protein-like (APPL), the fly homolog of the human amyloid precursor protein involved in Alzheimer’s disease. Western analysis revealed that the loe mutation reduces APPL processing, whereas overexpression of Loe increases it. These results describe a novel function of AMPK in neurodegeneration and APPL/APP processing which could be mediated through HMG-CoA reductase and cholesterol ester.